2000
DOI: 10.1046/j.1523-1755.2000.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of developing glomeruli in human fetal kidneys, See Editorial by Oliver and Al-Awqati, p. 2167

Abstract: In human glomerulogenesis, we demonstrate that fetal mesangial and capillary endothelial cells change their immunohistochemical phenotypes with maturation. They gradually lose fetal immunohistochemical phenotypes. Already before birth, the mesangial cells in almost all glomeruli at the late M stage acquire the adult phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 20 publications
7
48
0
Order By: Relevance
“…Moreover, nestin/vimentin doublelabeled cells clearly resembled podocytes, displaying long immunoreactive primary processes ( Figures 1G-1I). Double-labeling experiments carried out using nestin and the endothelial marker CD31 (Naruse et al 2000) showed that the relationships occurring between nestinpositive cells and endothelial cells were those expected between podocytes and the glomerular capillaries ( Figures 1J-1L).…”
Section: Adult Kidneymentioning
confidence: 69%
See 2 more Smart Citations
“…Moreover, nestin/vimentin doublelabeled cells clearly resembled podocytes, displaying long immunoreactive primary processes ( Figures 1G-1I). Double-labeling experiments carried out using nestin and the endothelial marker CD31 (Naruse et al 2000) showed that the relationships occurring between nestinpositive cells and endothelial cells were those expected between podocytes and the glomerular capillaries ( Figures 1J-1L).…”
Section: Adult Kidneymentioning
confidence: 69%
“…For this reason, in a single section of fetal kidney it is possible to appreciate all the stages of glomerular development in a sort of gradient of maturation going from the surface to the depth of the organ. The steps of glomerular maturation are morphologically divided into the following stages: vesicle (V), S-shaped body (S), capillary loop (C), and maturing glomerulus (M) (Naruse et al 2000;Pavenstä dt et al 2003). At low magnification, nestin staining on fetal kidney sections clearly appeared located in glomeruli at all the maturation stages ( Figure 4A).…”
Section: Fetal Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…46 During normal postnatal renal development in rats, the α-SMA cytoskeletal protein is expressed more intensely in the glomeruli, interstitium and peritubular capillaries, but α-SMA expression is restricted to arteriole and artery walls when the above mentioned structures mature. 47 Madsen et al 48 showed that the treatment of rats with the AT 1 antagonist candesartan for two weeks after birth reduced the total length, volume and surface area of capillaries in both cortex and medulla and disrupted vasa recta bundle organizations. These animals exhibited α-SMA-positive spindle-shaped cells that predominantly populated the outer medullary interstitium and the cortical medullary rays.…”
Section: Discussionmentioning
confidence: 99%
“…However, in various types of glomerular injury, the mesangial cell may acquire characteristics of a myofibroblast, which may in fact be injurious to the glomerulus. In human glomerulogenesis, mesangial cells gradually lose fetal phenotypes identified by alpha-smooth muscle actin [24]. However, with certain pathogenic stimulators, such as platelet-derived growth factor, mesangial cells may acquire smooth-muscle-like properties, characterised by the de novo expression of alpha-smooth muscle actin, and by the development of fibroblast-like properties, characterised by the production of interstitial collagens in addition to normal mesangial matrix constituents [25].…”
Section: Mouse Model Of Type 2 Diabetesmentioning
confidence: 99%